Family Literacy Toolkit - Literacy Quebec (LQ) (2021)

Soutenir les enfants et les familles anglophones en Gaspésie et aux Îles-de-la-Madeleine - Community Health and Social Services Network (CHSSN) (2019)
Bright Beginnings est une approche adaptée pour aider les enfants et les familles d’expression anglaise de la Gaspésie et des Îles-de-la-Madeleine. L’initiative est née d’une collaboration entre CASA, CAMI et VGPN, qui ont commencé à travailler avec des partenaires régionaux et locaux pour mieux adapter les programmes et les services afin de soutenir les enfants d’expression anglaise de 0 à 5 ans et leurs familles. Le Réseau communautaire de santé et de services sociaux (RCSSS) a adopté cette approche comme cadre de référence provinciale pour les communautés d’expression anglaise.

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands - Community Health and Social Services Network (CHSSN) (2019)
Bright Beginnings is an adapted approach to supporting English-speaking children and families in the Gaspé and Magdalen Islands. It originated through a collaboration between CASA, CAMI and VGPN who began to work with regional and local partners to better adapt programs and services to support English- speaking children 0 to 5 years old and their families. This approach has been adopted by the CHSSN as a provincial framework for English- speaking communities.

Your Family Makes a Difference - Leading English Education and Resource Network (LEARN)

Family Literacy Toolkit : Resources, Planning Guide, Best Practices - Literacy Quebec (LQ)
Literacy Quebec is a network that connects and represents community-based literacy organizations to empower people, impact lives and build a stronger society. We envision a Quebec where everyone has the literacy skills they need to live a fully engaged life.